2012
DOI: 10.1093/chemse/bjs083
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Affective Responses to Odors: Culture, Gender, and Olfactory Knowledge

Abstract: Emotion and odor scales (EOS) measuring odor-related affective feelings were recently developed for three different countries (Switzerland, United Kingdom, and Singapore). The first aim of this study was to investigate gender and cultural differences in verbal affective response to odors, measured with EOS and the usual pleasantness scale. To better understand this variability, the second aim was to investigate the link between affective reports and olfactory knowledge (familiarity and identification). Respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
122
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 49 publications
16
122
2
2
Order By: Relevance
“…One way to tackle this issue would be to present another odor that would be neutral enough not to constitute a primary reward but would be similarly rich to the chocolate in term perceptual characteristic. However, given the vast interindividual variability in hedonic odor perception (e.g., Delplanque et al, 2008;Distel et al, 1999;Ferdenzi et al, 2013), it appears very difficult to find a consensual neutral odor. Moreover, the learning process to associate two neutral stimuli is different from the one to associate an emotional stimulus with a neutral one.…”
Section: Discussionmentioning
confidence: 99%
“…One way to tackle this issue would be to present another odor that would be neutral enough not to constitute a primary reward but would be similarly rich to the chocolate in term perceptual characteristic. However, given the vast interindividual variability in hedonic odor perception (e.g., Delplanque et al, 2008;Distel et al, 1999;Ferdenzi et al, 2013), it appears very difficult to find a consensual neutral odor. Moreover, the learning process to associate two neutral stimuli is different from the one to associate an emotional stimulus with a neutral one.…”
Section: Discussionmentioning
confidence: 99%
“…When using a specific range of products, it is very likely that only one type of function would be targeted, thus automatically weakening the discriminative power of the EOSs, which may also miss affective aspects related to that specific category of products. Indeed, EOSs do not attach to the odor and the EOSs responses to it has been studied and described elsewhere (Ferdenzi et al 2013). Therefore, another limit of our tool is that there is some uncontrolled variation in the affective response to odors due to associated products and contexts in memory (e.g., food vs. nonfood contexts).…”
Section: Some Of Them Are Clearly or Slightly Negatively Connoted (Nementioning
confidence: 99%
“…Previous studies have demonstrated links between familiarity and pleasantness of odours (e.g. Distel et al 1999;Ferdenzi et al, 2013), which may underpin this relationship, especially as correlations between familiarity and odour pleasantness are stronger for pleasant than unpleasant odours (Delplanque et al, 2008).…”
Section: Discussionmentioning
confidence: 99%